Rapid nutrient evaluation of sorghum silages using two types of near-infrared reflectance spectroscopy - K.J. Budiongo; L.H. Harbers; B.W. Seabourn; K.K. Bolsen; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1997)
This research was designed to develop a set of prediction equations to measure nutrient composition of Kansas sorghum silages using both a portable and a research type near-infrared spectrometer (NIRS). A robust set of equations for dry matter, crude protein, neutral detergent fiber, and acid detergent fiber was developed for a wide range of sorghum phenotypes . NIRS analysis of sorghum silages is feasible with both a tilting filter (portable) and research instrument with a grating monochrometer.
Keywords: Cattlemen& #x27; s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Sorghum silage; Nutrient content; Near-infrared reflectance spectroscopy